The Distance between N and C Termini of Tau and of FTDP-17 Mutants Is Modulated by Microtubule Interactions in Living Cells - Di Primio, Cristina; Quercioli, Valentina; Siano, Giacomo; Rovere, Matteo; Kovacech, Branislav; Novak, Michal; Cattaneo, Antonino (Frontiers in Molecular Neuroscience, 2017)
The microtubule-associated protein Tau is a natively unfolded protein, involved in a number of neurodegenerative disorders, collectively called tauopathies, aggregating in neurofibrillary tangles (NFT). It is an open question how the conversion from a microtubule (MT) bound molecule to an aggregation-prone Tau species occurs and, also, if and how tauopathy-related mutations affect its behavior in the cell. To address these points, we exploited a genetically encoded FRET sensor based on the full length Tau protein, to monitor in real time Tau conformational changes in different conditions in live cells. By studying the FRET signal we found that soluble Tau molecules, detached from MTs, display an unfolded structure. On the contrary, we observed an increased FRET signal generated by Tau monomers bound to MT, indicating that the association with MTs induced a folding of Tau protein, decreasing the distance between its N and C termini. We exploited the FRET sensor to investigate the impact of FTDP-17 mutations and of phosphorylation-site mutations on Tau folding and mobility in live cells. We demonstrate that the FTDP-17 Tau mutations weaken the interaction of Tau with cellular MTs, shifting the equilibrium towards the soluble pool while, conversely, phosphorylation site mutations shift the equilibrium of Tau towards the MT-bound state and a more closed conformation.